Heterochronic Parabiosis Approach: is it Possible to Interrupt the Aging Process of the Intervertebral Disc Degeneration? An in vivo Experimental Study. Issue 1 (April 2016) - Colangelo, Debora; Robbins, Paul; Nasto, Luigi Aurelio; Niedernhofer, Laura; Pola, Enrico
Introduction: Low back pain is a chronic health problem. It is the most common cause of limited activity. 90% of people worldwide will develop low back pain during their life. It is due, in the most cases, to the intervertebral disc degeneration (IDD). The first cause of IDD is aging. In all tissues aging is a condition characterized by mutations and genome instability, mitochondrial dysfunction, oxidative damage and consequential decline of cellular functions. Decline in tissues function is related to the loss of stem cells. These characteristics translate into different pathologies, with increasing costs for the healthcare system. In 2050 around 2 billion people worldwide will be older than 65. People are living longer but they are not healthier. Worldwide research is focused on identify the molecular pathways that can regulate expression of pro-survival networks. The purpose of this study was to determinate whether blood chimerism with a young wild type mouse (WT) could delay or reverse aging in a prematurely aging mouse model (Ercc1-/Δ). Blood chimerism was obtained by way of parabiosis, an experimental method in which two animals are surgically connected and develop a united circulation. Material and Methods: 3 kinds of parabiotic pairs were generated: WT + WT at 40 days old (hisochronic parabiosis), Ercc1-/Δ + Ercc1-/Δ at 64 days old (hisochronic parabiosis) and WT + Ercc1-/Δ (heterochronic parabiosis). After surgery the couples develop anastomosis that make possible the blood chimerism. Administration of a dye (Evans blue) and fluorescent nano-beads into a single symbiont animal were used to test shared circulation in the parabiosis couples. Mice were sacrificed after 4 weeks; entire intervertebral discs were removed from the surrounding vertebral bodies by an incision along the endplate. Lumbar discs from each mouse were analyzed histologically and for nucleous polposus protein content. Expression of pro-survival networks in senescent cells and in stem cells were analyzed. Results: Compared with the hisochronic controls, Ercc1-/Δ mice heterochronically paired with young WT mice had a significally improved protein content in the disc (95% CI). Histological analysis (EE & SaffO) revealed an improvement in the disc for the Ercc1-/Δ individual in the heterochronic pair relative to the hisochronic ones. We observed a reactivation of stem cells when exposed to younger serum and a migration of young stem cells to the old mice (using GFP protein expressed in the younger mouse). Furthermore µCT highlighted an improvement of the bone quality. Conclusion: These results indicate that spine of the progeroid mice were rejuvenated in the older mice when exposed to a serum derived from younger organism. Senescent cells secrete pro-inflammatory cytokines, and chemokines, which together constitute the senescence-associated secretory phenotype. We believe that stem cells are quiescent in old organism and that the environment can reactivate them. Moreover this factor can attract young stem cells from the young mice. The factor responsible for this, this elixir of youthful, although currently unidentified, could potentially be used as an effective treatment to rescue IDD as well other pathologies connected to aging.